2016
DOI: 10.3390/children3040034
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Risk Factors and Genu Valgum Conducive to the Onset of Growing Pains in Early Childhood

Abstract: The most prevalent musculoskeletal disorder of childhood with unclear aetiology is growing pains (GPs). Anatomic deformities and factors that change bone turnover are implicated in GP pathophysiology. Perinatal risk factors alter the bone metabolism affecting the bone mineral density and content. The aim of our study was to analyze the relationship between GPs, knock knees and perinatal factors. The examined population consisted of 276 children aged 3–7 years. Among them, ten pairs of dizygotic twins were eval… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…6 If the longitudinal axis of the knee joint is not aligned by then, and the IMD is more than 5cm, 7 physiotherapeutic intervention is called for. The degree of GV has a significant effect on the development of growing pains 8 and orthrosis because the imposed loads are no longer equally distributed between the outer and the inner halves of the knee. 9 This is the best time-period for deflexion correction.…”
Section: Introductionmentioning
confidence: 99%
“…6 If the longitudinal axis of the knee joint is not aligned by then, and the IMD is more than 5cm, 7 physiotherapeutic intervention is called for. The degree of GV has a significant effect on the development of growing pains 8 and orthrosis because the imposed loads are no longer equally distributed between the outer and the inner halves of the knee. 9 This is the best time-period for deflexion correction.…”
Section: Introductionmentioning
confidence: 99%
“…Kaspiris et al[16] analyzed the association of the onset and intensity of growing pains with some perinatal risk factors. The study revealed that a short gestation period, low Apgar score, low birth length or weight, and lower head circumference were positively correlated with the development of growing pains in childhood.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Evans and Shutter[20] found in a cohort of 180 patients only a weak correlation between foot posture and the child’s functional health and no longer supports the anatomical theory. In 2016, Kaspiris et al[16] found a positive correlation with genu valgum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several other proposed hypotheses for growing pains, including anatomical factors such as at feet, over-pronated feet, and joint hypermobility [24][25][26][27][28], lower pain threshold [29,30], lower skeletal vascular perfusion [24,31], reduced bone strength [32,33], and psychological factors [34][35][36]. Various factors, individually or in association, might be responsible for the onset of growing pains.…”
Section: Discussionmentioning
confidence: 99%